Comparative evaluation of propofol and etomidate for laryngeal mask airway insertion and hemodynamic stability: A randomized controlled trial. - Gundeboyina, Dr. Haritha; Gulipalli, Dr.Harikrishna; Siddarth, Dr. Pigilam (Student's Journal of Health Research Africa, 2025)
Background The laryngeal mask airway (LMA) is widely used in modern anesthesia practice, and successful insertion requires adequate suppression of airway reflexes with minimal hemodynamic disturbances. Propofol is considered the standard induction agent but is associated with hypotension, whereas Etomidate offers cardiovascular stability, though insertion conditions may be suboptimal. Aim: To compare the ease of LMA insertion and hemodynamic responses following induction with intravenous Propofol and Etomidate. Methods This prospective randomized double-blind study included 62 ASA I–II patients aged 18–50 years, undergoing elective surgeries at CARE Hospitals, Visakhapatnam. Participants were randomly assigned to receive either Propofol (2 mg/kg; n=31) or Etomidate (0.3 mg/kg; n=31) for induction. Ease of LMA insertion was evaluated using predefined parameters (mouth opening, gagging, coughing, head/limb movements, and laryngospasm). Hemodynamic variables (heart rate, systolic and diastolic blood pressure) were recorded at baseline and 30 seconds post-induction. Results The mean age was 32.1 ± 8.0 years; both groups were comparable in gender (Propofol 58% male vs. Etomidate 55% male), weight (61.2 ± 9.6 kg vs. 60.4 ± 8.8 kg), and ASA status (Grade I: 67.7%, Grade II: 32.3%). Propofol achieved better insertion conditions with higher adequate mouth opening (93.5% vs. 71.0%, p=0.02), absence of gagging (90.3% vs. 61.3%, p=0.01), and first-attempt success (93.5% vs. 74.2%, p=0.04). However, Propofol caused significant post-induction hypotension (SBP 124 → 98 mmHg; p<0.001), while Etomidate maintained stable hemodynamics. Conclusion Propofol provides better ease of LMA insertion with higher first-attempt success but is associated with significant hypotension. Etomidate, although hemodynamically stable, offers less favorable insertion conditions. The choice between the agents should therefore balance airway insertion ease against cardiovascular safety. Recommendations Propofol is preferred for healthy patients; Etomidate is recommended in cardiovascularly vulnerable individuals to balance airway management and hemodynamic stability.